Labour market reforms and current account imbalances: beggar-thy-neighbour policies in a currency union? - Baas, Timo; Belke, Ansgar (Brussels, 2014)
"Member countries of the Economic and Monetary Union (EMU) initiated wide-ranging labour market reforms in the last decade. This process is ongoing as countries that are faced with serious labour market imbalances perceive reforms as the fastest way to restore competitiveness within a currency union. This fosters fears among observers about a beggar-thy-neighbour policy that leaves non-reforming countries with a loss in competitiveness and an increase in foreign debt. Using a two-country, two-sector search and matching DSGE model, we analyse the impact of labour market reforms on the transmission of macroeconomic shocks in both non-reforming and reforming countries. By analysing the impact of reforms on foreign debt, we contribute to the debate on whether labour market reforms increase or reduce current account imbalances."